2014
DOI: 10.1107/s160057751401697x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose and image quality inK-edge subtraction computed tomography of lungin vivo

Abstract: K-edge subtraction computed tomography (KES-CT) allows simultaneous imaging of both structural features and regional distribution of contrast elements inside an organ. Using this technique, regional lung ventilation and blood volume distributions can be measured experimentally in vivo. In order for this imaging technology to be applicable in humans, it is crucial to minimize exposure to ionizing radiation with little compromise in image quality. The goal of this study was to assess the changes in signal-to-noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Additionally, the typical beam size provided by a synchrotron is far below the beam size needed for clinical diagnostics. Over the past decades, Compact Synchrotron Sources have been developed as an alternative means to serve the need for high monochromatic flux X-ray beams and may have the potential to make KES imaging available in a clinical setting in the future 16 . Currently many projects to build inverse Compton sources are ongoing, such as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the typical beam size provided by a synchrotron is far below the beam size needed for clinical diagnostics. Over the past decades, Compact Synchrotron Sources have been developed as an alternative means to serve the need for high monochromatic flux X-ray beams and may have the potential to make KES imaging available in a clinical setting in the future 16 . Currently many projects to build inverse Compton sources are ongoing, such as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…First, the dose of ionizing radiation is a limiting factor. However, recent studies have demonstrated that KES-CT can be performed with an air kerma of 40 mGy, which is within the range or only slightly above the range of clinically applicable doses 22 . Second, although the contrast sensitivity of KES CT is limited and inferior to radionuclide or fluorescent imaging, the smallest detectable concentration of iodine is 185 µg/ml, and even lower for gadolinium: 81 µg/ml 23 .…”
Section: Discussionmentioning
confidence: 97%
“…Gating also enabled good correlation between the iodine and xenon KES image acquisitions, such that the same locations in the lungs were imaged. Our gating technique is different from previously published studies as the images were obtained in breathing animals, whereas others have paused the ventilator to image during apnea (Monfraix et al, 2005;Strengell et al, 2014;. We expect that our technique will provide more physiologically relevant conditions to obtain quantitative measurements of air content in the lungs, blood volume, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging was performed following introduction of 80% Xe in O 2 and obtaining images during a 60 s apnea induced by pausing the ventilator at the end of inspiration and during functional residual capacity (Monfraix et al, 2005). In another study, the radiation dose and image quality were studied for rabbits imaged with 70% Xe in O 2 or 20% Xe in O 2 (Strengell et al, 2014). Following 21 breaths to reach steady state, the ventilator was paused for 3 s to obtain the images, with the authors concluding that low radiation doses acceptable for patient use were achievable with adequate image quality, but higher Xe concentrations were required which may lead to anaesthetic effects in the patient.…”
Section: Introductionmentioning
confidence: 99%